2015
DOI: 10.1038/jid.2015.104
|View full text |Cite
|
Sign up to set email alerts
|

EphB2 Promotes Progression of Cutaneous Squamous Cell Carcinoma

Abstract: Keratinocyte-derived skin cancer, cutaneous squamous cell carcinoma (cSCC), is the most common metastatic skin cancer. We have examined the role of Eph/ephrin signaling in the progression of cSCC. Analysis of the expression of EPH and EFN families in cSCC cells and normal epidermal keratinocytes revealed overexpression of EPHB2 mRNA in cSCC cells and cSCC tumors in vivo. Tumor cell-specific overexpression of EphB2 was detected in human cSCCs and in chemically induced mouse cSCCs with immunohistochemistry, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 48 publications
1
63
0
Order By: Relevance
“…EphB2, a receptor tyrosine kinase for ephrin ligands, is overexpressed in a variety of cancers and plays an important role in cancer progression. [26][27][28] Before our research, only EphB2 messenger RNA (mRNA) transcription level in small cell lung carcinoma has been reported but no protein expression, distribution, or survival analysis is shown. 29 So far, we first reported that EphB2 was predominantly overexpressed in cell membranes and cytoplasm of lung AC tissues, and low EphB2 expression in lung AC predicted better survival and low mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…EphB2, a receptor tyrosine kinase for ephrin ligands, is overexpressed in a variety of cancers and plays an important role in cancer progression. [26][27][28] Before our research, only EphB2 messenger RNA (mRNA) transcription level in small cell lung carcinoma has been reported but no protein expression, distribution, or survival analysis is shown. 29 So far, we first reported that EphB2 was predominantly overexpressed in cell membranes and cytoplasm of lung AC tissues, and low EphB2 expression in lung AC predicted better survival and low mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that EphA subfamily is tumor suppressors, considering the fact that low concentration of EphA1 was identified in nonmelanoma skin cancer and low levels of EphA2 favour the development of chemically induced skin cancer in mice [124]. In cSCC, EphB2 determines proliferation, migration, and invasion, thus becoming the object of possible targeted therapies [125]. Farshchian et al [125] identified high levels of EphB2 in primary and metastatic cSCC cells through microarray, qRT-PCR, and next-generation sequencing.…”
Section: Proteic and Other Potential Biomarkers Of Squamous Cell Cmentioning
confidence: 99%
“…In cSCC, EphB2 determines proliferation, migration, and invasion, thus becoming the object of possible targeted therapies [125]. Farshchian et al [125] identified high levels of EphB2 in primary and metastatic cSCC cells through microarray, qRT-PCR, and next-generation sequencing. These receptors were found on the surface of cSCC cells (clustered and bound with their ligands) as well as in the cytoplasm [125, 126].…”
Section: Proteic and Other Potential Biomarkers Of Squamous Cell Cmentioning
confidence: 99%
See 1 more Smart Citation
“…(77,81) The Eph receptors/ephrins have also been implicated in tumourigenesis, progression and metastasis across a wide range of malignancies (Table 3). ( (83) Prostate cancer (84,85) Breast cancer (86,87) Melanoma (88) Glioblastoma (89,90) Gastric cancer (91) EphA3 Gastric cancer (92) Colorectal cancer (93) EphB2 Advanced cSCC (94) Glioblastoma (95)(96)(97) Cervical cancer (98) Breast cancer (99) EphB4 HNSCC (100) Non-small cell lung cancer (101) Breast cancer (99) Downregulated EphA1 NMSC (77) …”
Section: Galaninmentioning
confidence: 99%